An informative mosque application via hybrid technology using geofencing technique / Ahmad Shamsyahiran Ahmad Rohisham - Ahmad Rohisham, Ahmad Shamsyahiran (2019)
Mosque is a place where Muslim gather and do their prayers. However, some mosque usually has many other activities planned throughout the week or month. For example, lecture on fiq, usrah, campaign etc. The main problem is the number of participants attend these activities and how to spread the existent of these activities. Hence, the objective of this project is to help mosque increase number of participants in their activities by providing them with information when they are nearby mosque location. Furthermore, to help the mosque management to ease their job in managing the event. For this project, a geolocation method will be apply that usually been use by any other companies to advertise their products. The geolocation technique will notify any user that are inside the geographical area on info about the mosque activities.